North-South collaboration: On the making of a Center for Comparative Education and Policy Studies at Addis Ababa University - Haybano, Alebachew Kemisso; Haley, Aimee; Lindblad, Sverker; Wärvik, Gun-Britt (Nordic Journal of Comparative and International Education (NJCIE), 2021)
The Ethiopian educational system has made promising advancements since the turn of the century. Despite this progress, education continues to grapple with a myriad of challenges, including differences in educational access and quality, insecure living conditions, and gender inequalities. Research can offer knowledge for tackling these challenges, but often it is knowledge from the global North that dominates, despite its questionable relevance to the global South. Therefore, this study analyses the evolvement of a Center for Comparative Education and Policy Studies, situated in an Ethiopian higher education context and supported by the Swedish International Development Cooperation Agency (SIDA), and how the Center has contributed to developing knowledge that is relevant to local contexts. An important outcome of the Center was the development of a doctoral program in International and Comparative Education and the knowledge produced in the doctoral theses that emerged. Our inquiry concerns how Southern theory contributes to an increased understanding of the development of the Center and the relevance of the doctoral theses. The findings underscore the importance of expanding Southern knowledge in education and the need for further reflection on the geopolitics of knowledge in research capacity development cooperation.